A document-oriented web-based application for supporting collaborative product development - Rocha, Filipe (2010)
Innovation is a creative process strongly associated with development and deployment of new products, i.e., goods and services. This is essential in the global economy of today for sustainability and success of companies. Good collaboration between those involved in new product development is an essential requisite for this success. Such collaboration, which involves not only company stakeholders but also suppliers and customers, requires easy access to necessary data and agile communication and sharing of relevant information, which is distributed in a network of resources and users. Hence, web-based applications, decentralized repositories and databases are used to store and manage product and process development information. For meeting these new product development requirements Internet based collaborative tools and services must be applied. The use of web services is important in product development, helping the integration of data and knowledge bases and also processes and application interactions.This paper reports on work for managing product and process information, as well as documentation generation, throughout the product development process cycle in an Internet based collaborative environment. The information concerned includes product and process information, as well as product development history. One important aspect deals with web based restoring decisions and options made along the product design and development cycle, including product revisions and/or versions manipulation. The research work, focus is on the development of a document- oriented web-based application using Apache CouchDB technology and REST web services. The proposed application is described and the main functionalities are illustrated through some examples of use.